Effective EFL Teachers as Viewed by Senior High School - Ulfah Alfiyyah Abu; Abdul Halim (Universitas Negeri Makassar, 2017)
This research aimed to investigate the characteristics of effective EFL teachers as viewed by the students and various characteristics of effective EFL teachers as viewed by the different students’ English achievement. This research was designed by using qualitative research. This research applied purposive sampling technique. The participants of this research were two classes of SMA Negeri 17 Makassar in the academic year 2015/2016. The data was collected through class discussion and individual interview. The results of this research suggest that EFL teachers are need to focus on 15 characteristics indicated effective EFL teachers based on government rules (Permendiknas number 16/2007) which are placed into four categories, they are pedagogical, personal, professional, and social competences and in addition, teachers need to improve their academic qualification, pay attention to physical appearance, and adopt the characteristics of younger and female teachers as the most favored by the students. Furthermore, the different students’ achievement affects their view of various characteristics of effective EFL teachers covering assessment and evaluation, learning process, the use of social media, what should be understood, and appearance.